Multireference configuration interaction calculations on the FeS molecule. (3rd July 2022) - da Silva, Ramon S.; Ballester, Maikel Y.
ABSTRACT: High-level ab initio calculations for the A 5 Σ + -X 5 Δ and the a 7 Σ + -X 5 Δ band systems of the FeS molecule are here reported. For such, potential energy curves are calculated using the multireference configuration interaction (MRCI) method. Subsequently, the computed interaction energies were fitted to an analytical representation and a new set of spectroscopic parameters was derived. The calculations predict a dissociation energy of 27, 015 cm − 1 for the X 5 Δ, in agreement with recent experimental measurements. The similarity between X 5 Δ and A 5 Σ + is considerable, showing an energy separation of only 953  c m − 1 . The spin-orbit coupling (SOC) effect was considered by using the Breit-Pauli operator ( H ˆ S O ). At the equilibrium distance, the obtained SOC constant for the ground state is A e (X 5 Δ )= −206.6 cm − 1 . The rotationless radiative lifetimes for the A 5 Σ + and a, 7 Σ + excited states are in the orders of milli- and microseconds, respectively, indicating that the vibronic emissions of the A 5 Σ + -X 5 Δ system are too weak to be observed. GRAPHICAL ABSTRACT: UF0001